2013
DOI: 10.1002/jcu.22082
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and management of a massive fetal ovarian hemorrhagic cyst torsion with secondary fetal anemia

Abstract: We report the case of one of the largest prenatally detected fetal hemorrhagic cyst with ovarian torsion and fetal anemia leading to subsequent cesarean section delivery and further unilateral oophorectomy of the neonate. Usually, fetal ovarian cysts tend to resolve spontaneously within the first months after birth. There is no need of surgical treatment for such simple cysts. Routine sonographic examinations are obligatory, because in some cases complications such as massive hemorrhage, cyst rupture, or ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although rare, other complications of fetal ovarian cysts are noteworthy. There have been several publications of haemorrhage into the cyst significant enough to cause fetal anaemia requiring transfusion or delivery . Another case report described displacement of thoracic organs because of the sheer size of the cyst, which had grown to 100 mm by the 30th week of gestation, and prenatal aspiration was employed .…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, other complications of fetal ovarian cysts are noteworthy. There have been several publications of haemorrhage into the cyst significant enough to cause fetal anaemia requiring transfusion or delivery . Another case report described displacement of thoracic organs because of the sheer size of the cyst, which had grown to 100 mm by the 30th week of gestation, and prenatal aspiration was employed .…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the presence of complex ovarian cysts indicates the need for surgical exploration: some authors proposes surgical excision in case of neoplastic suspicion, in cases of complex ovarian cysts and when simple cysts remain unchanged for more than 6 months. 10,32,33 However, the finding of complex ovarian cysts does not place an absolute indication to surgery: 3,34 authors reported a spontaneous tendency towards involution of twisted ovarian cysts, concluding that conservative treatment of such cysts may represent a therapeutic option and that surgery should be reserved for particularly large lesions (when it results in an intra-abdominal mass effect) or those that do not tend to involve. 4 However, conservative treatment of complex ovarian cysts, however, does not reduce the risks of possible complications, which, although rare, have important clinical implications: 21 there are several publications reporting the correlation between intracystic hemorrhage and development of fetal, or neonatal, anemia requiring transfusion therapy; 35,36 moreover postnatal intestinal obstruction caused by complex ovarian cysts is also described: the presence of self-amputated ovarian cysts can cause inflammation and intestinal adhesions (the risk of intestinal obstruction due to amputated cysts has not been compared to that caused by laparoscopic exploration, and there are divergent opinions on this aspect).…”
Section: Surgical Approachmentioning
confidence: 99%